Effects of Whole-Body Vibration on Upper Extremity Function and Grip Strength in Patients with Subacute Stroke: A Randomised Single-Blind Controlled Trial - Jin-Young Ahn; Hyeongsu Kim; Chan-Bum Park (Occupational Therapy International)
Background. Whole-body vibration has been used to improve motor function in chronic stroke patients, but its effect on patients with subacute strokes remains unclear. Objectives. We explored the effect of whole-body vibration on patients with subacute strokes. Methods. Participants were randomly allocated to a whole-body vibration (WBV) group (n=30) or an upper- and lower-cycle (ULC) group (n=30). Both groups received occupational therapy after these interventions. All participants received treatment for 30 min/day, 5 days/week, for 4 weeks. Both groups received the same conventional physical therapy. Results. The manual function test (MFT) score and grip strength improved after both WBV (p=0.001 and p=0.001, respectively) and ULC (p=0.002 and p=0.001, respectively), but the improvement was more pronounced (MFT p=0.016; GS p=0.023) after WBV. Conclusions. These findings suggest that the use of WBV and ULC was effective as remedial treatments for improving upper extremity motor function and increasing grip strength for patients with subacute strokes. The improvement was more pronounced for the WBV treatment. This trial is registered with KCT0003246.